A construção verbo-imagética do referente em anúncios publicitários de veículos - Silva, Luciene Helena da (2020)
The studies developed in the context of Textual Linguistics (LT) have devoted special attention to the phenomenon of Referencing (KOCH, 2004; CAVALCANTE, 2011, 2015) and, more recently, Multimodality. Inserting ourselves in this investigative path, our research analyzes the construction and reference recategorization in advertisements, essentially multimodal genders (RODRIGUES, 2016). Knowing that the referring ones are currently understood as objects constructed in and by the discourse (MONDADA, 1994), we aim to analyze how their construction occurs in verb-imagery texts, that is, which elements contribute to (re) construction and for the recategorization of the reference and how this occurs. In order to achieve this goal, we will use as analytical categories the Representational, Interactive and Compositional metafunctions, arising from the Grammar of Visual Design (GVD), proposed by Kress and van Leeuwen (2006, [1996]). Regarding to recategorization, we follow the studies developed by Lima (2009, 2017 and 2018), mainly, so the author proposes about imagery reference recategorization. The corpus of the research consists of 85 vehicle commercials, collected on Brazilian sites of automakers, which were analyzed from metafunction, starting with Interactive Metafunction, followed by representational metafunction and ending with metafunction Compositional. Based on these analyses, we verified how the introduction of the Vehicle works, its construction and recategorization, seeking to identify the visual syntax built in the commercial. About Interactive Metafunction we observe that: 1) In the subclass "Look" the vehicle is in offer position; 2) In the subclasse "Social distance", appears in OPEN PLAN; In the subclass "Perspective", appears at an oblique angle. However, due to the specific characteristics of the announced, we feel the need to admit the existence of the LATERAL angle, not provided by Kress and van Leeuwen (2006) and 3) In the subclass “Modality” predominates as A NATURALIST. We note that the subclass "Look" directly relates to with the subclass "Narrative" of representational metafunction. In this metafunction, we realized that the ads were mostly produced from a NON-TRANSACTIONAL ACTION NARRATIVE. Thus, the announced vehicle is the actor, the only participant responsible for the narrative, since, even in advertisements, in the which he does not appear alone, he configures himself as the focus of information, exercising the subject role of visual syntax. Concerning the compositional metafunction, our analyses indicate that the most widely used triptych space in the ads vehicle advertising are those intended for information given and the region of the Center. We also note that there is a close relationship between the categories framing and boss. Typographical features, such as font type and size, colors, brightness, contrasts and visual effects contribute greatly to the construction of senses, because they evidence the most important information, pointing to the elements that present themselves as a referential introduction and those in which concentrate the process of construction and recategorization. In short, we consider that the categories proposed by the GDV contribute to the understanding of the phenomenon of Reference, enabling relevant analyses on how the referring ones are constructed and recategorized in multimodal discursive genres. Although we have found that metafunctions provide evidence of what elements are configured as IR, however, this choice will depend on the reader, consequently, resulting in in choosing the elements responsible for recategorization. We believe that our research, when analyzing the construction and reference recategorization in advertisements vehicle advertising through categories arising from the GDV, indicates the visual syntax used in these genres, thus contributing to reading and interpreting multimodal genres.